Capture One Pro 9 mastering raw development, image processing, and asset management - Erni, Sascha (Rocky Nook, 2016)
Whether you're moving to Capture One Pro from Aperture or Lightroom, or just beginning to learn image-editing with Capture One Pro 9, this book will teach you how to get amazing results while avoiding frustration and wasted time along the way. --
Title of the German original: Praxis Capture One Pro 8, published by dpunkt.verlag, ©2015. - Includes bibliographical references. - Online resource; title from title page (Safari, viewed February 5, 2016)
Keywords: Image processing -- Digital techniques; Photography -- Digital techniques; Traitement d'images; Techniques numériques; Photographie numérique; digital imaging; Image processing; Digital techniques; Photography; Digital techniques; Anleitung.